Evaluasi Pelaksanaan Sistem Informasi Manajemen Sekolah (SIMAS) Penerimaan Peserta Didik Baru (PPDB) Online SMK Pariwisata Triatma Jaya Badung - N.G.A.S. Astadi; I.G.K.A. Sunu; I.N. Natajaya (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aims to determine the results of the evaluation separately or together in the Context, Input, Process, and Product, also finding obstacles occur in the implementation of SIMAS PPDB Online. This research is a program evaluation research with the CIPP (Context, Input, Process, and Product) model. About 66 teachers from SMK Wisata Triatama Jaya Badung were sampled in this study. Data were collected through a questionnaire with a Likert score. This research uses quantitative descriptive analysis method to determine the effectiveness of the implementation of SIMAS PPDB Online. Quantitative results obtained the effectiveness of the implementation of SIMAS PPBD Online in terms of the CIPP showing positive (+) results in every element. Overall the results shows of CIPP are very effective (+ + + +). The obstacles found in this research are: (1) Less extensive internet coverage, (2) There are teachers who don’t understand technology, 3) Lack of SIMAS PPDB development staff, 4) Reporting on SIMAS PPDB funding is not clear enough